(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article very clearly reveals the study of the prevalence and determination of risk factors for the occurrence of CDI, as well as a retrospective analysis of the case histories of patients with various malocclusion deformities in Bukhara. There have also been clinical studies of children conducted after the informed consent of the parents. For the study, the results of examination and orthodontic treatment of patients aged 6 to 18 years were used.